The Development of Hospitality and Tourism Industry in Africa - SKOBKIN, Sergey S.; MILORADOV, Konstantin A.; KOVALTCHUK, Andrey P. (Journal of Environmental Management and Tourism; Vol 11 No 2 (2020): JEMT Volume Xi Issue 2(42) Spring 2020DO - 10.14505//jemt.v11.2(42).04, 2020)
The article investigates the dynamics and factors affecting the development of the market of tourist services of the African continent. The authors analyze statistical data on the development of the hospitality and tourism industry, the influence of cultural, historical and modern political factors. African countries have not only rich cultural and historical traditions. Africa's hospitality and tourism industry has great potential for development. The results of the study allow us to build a statistically sound forecast of international arrivals in Africa and draw a conclusion about the prospects for the development of the hospitality industry and tourism in General. The growth of international arrivals is influenced by competition in the hotel market. The positive effect of hotel chains on Africa is obvious. The network strategy of hotel business development has shown itself positively in many countries of the world. The hospitality and tourism industry continues to develop rapidly – in the coming years, we can expect a significant increase in the number of international tourist arrivals, the growth of paid services, the growth of the number of rooms.